2020
DOI: 10.1371/journal.pone.0236516
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral collagen signatures predict clinical outcomes in feline mammary carcinoma

Abstract: Breast cancer is the most common cause of cancer-related deaths in women worldwide. Identification of reliable prognostic indicators and therapeutic targets is critical for improving patient outcome. Cancer in companion animals often strongly resembles human cancers and a comparative approach to identify prognostic markers can improve clinical care across species. Feline mammary tumors (FMT) serve as models for extremely aggressive triple negative breast cancer (TNBC) in humans, with high rates of local and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 77 publications
(123 reference statements)
0
7
0
3
Order By: Relevance
“…Spontaneously occurring canine mammary gland tumors (CMT) have been proposed to have advantages as a model of human breast cancer compared to murine models, particularly when examining the tumor stroma 9 11 . In fact, recent work supports similarities between prognostic collagen signatures of women and female dogs and cats 12 16 , indicating that a comparative oncology approach provides valuable insights into the role of collagen in directing clinical behavior of breast cancer of veterinary and human patients. Recent studies have shown that aberrant collagen cross-linking is in part responsible for stiffening tumor ECM that facilitates cancer progression and metastasis 1 , 17 , 18 .…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Spontaneously occurring canine mammary gland tumors (CMT) have been proposed to have advantages as a model of human breast cancer compared to murine models, particularly when examining the tumor stroma 9 11 . In fact, recent work supports similarities between prognostic collagen signatures of women and female dogs and cats 12 16 , indicating that a comparative oncology approach provides valuable insights into the role of collagen in directing clinical behavior of breast cancer of veterinary and human patients. Recent studies have shown that aberrant collagen cross-linking is in part responsible for stiffening tumor ECM that facilitates cancer progression and metastasis 1 , 17 , 18 .…”
Section: Introductionmentioning
confidence: 78%
“…In order to elucidate the molecular mechanisms driving tumorigenesis and metastatic potential as well as to develop therapeutic strategies for human breast cancer, a number of animal models such as mice 75 , rats 76 , 77 , cats 16 , 76 80 , and dogs 9 , 81 – 84 have been developed. Given the protracted timeline and staggering expense of cancer therapies (estimated US ~ $1.8 billion to bring a new therapeutic from target validation to market) 85 , compounded by the high rate of failure (59% of anti-neoplastic drugs entering Phase III clinical trials) 86 , 87 , it is imperative to examine toxicity and efficacy in preclinical trials using a model that most closely mimics breast cancer in women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aggressive carcinomas with shorter collagen fibers are present in female dogs with mammary tumors, which directly affects survival time [34]. This has also been observed in feline mammary tumors, wherein denser collagen, thicker and straighter fibers, and less identifiable tumor-stromal boundaries are associated with poorer outcomes, independent of clinical variables, thus increasing the predictive power of the clinical model [35].…”
Section: Introductionmentioning
confidence: 91%
“…Na medicina veterinária foram realizados poucos estudos para o melhor entendimento dessa interação entre o câncer de mama e a MEC em comparação aos estudos humanos (Case et al, 2017;Rosen et al, 2020).…”
Section: Introductionunclassified